2015
DOI: 10.1016/j.visres.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A neural model of border-ownership from kinetic occlusion

Abstract: Camouflaged animals that have very similar textures to their surroundings are difficult to detect when stationary. However, when an animal moves, humans readily see a figure at a different depth than the background. How do humans perceive a figure breaking camouflage, even though the texture of the figure and its background may be statistically identical in luminance? We present a model that demonstrates how the primate visual system performs figure-ground segregation in extreme cases of breaking camouflage ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 57 publications
(84 reference statements)
0
14
0
Order By: Relevance
“…The primate visual system most likely uses several redundant and complementary mechanisms for all manner of computations, including DOFM. Thus models that use BF cues, such as that of Layton and Yazdanbakhsh (2015), could possibly be combined with the FMO model in order to take full advantage of all the available cues. For example, stimuli that are not random-dot based, where there are BF cues but no AD cues-such as the demos of Brooks and Palmer (2003)-cannot be explained by the FMO model.…”
Section: Discussionmentioning
confidence: 99%
“…The primate visual system most likely uses several redundant and complementary mechanisms for all manner of computations, including DOFM. Thus models that use BF cues, such as that of Layton and Yazdanbakhsh (2015), could possibly be combined with the FMO model in order to take full advantage of all the available cues. For example, stimuli that are not random-dot based, where there are BF cues but no AD cues-such as the demos of Brooks and Palmer (2003)-cannot be explained by the FMO model.…”
Section: Discussionmentioning
confidence: 99%
“…The heuristic used here assumes that an object is usually observed by a closed contour, and the center of this contour might be used to represent the location of this object. Since the focus of this work is on sensorimotor coordination rather than complex object recognition, the more complex cases of occlusion and boundary ownership are not taken into account (Heydt et al, 2003 ; Layton and Yazdanbakhsh, 2015 ; Dresp-Langley and Grossberg, 2016 ). To achieve our goal, we first applied a center-surround filter and convolved CPM's luminance profile regardless of depth, as shown in the grid in Figure 2D , where the filled pattern is an example and corresponds to what we actually used in the experiments.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…This temporal difference indicates that the KB‐orientation‐selective response is computed by using feedback inputs from some areas (Marcar et al., ). A model study also has suggested that V4 and MT neurons, which feed signals back to V2 neurons, can play a crucial role in determining figure surfaces distinct from the background using motion cues (Layton & Yazdanbakhsh, ) (Figure ).…”
Section: Early Cortical Areas Likely Provide a Key Function To Share mentioning
confidence: 99%